Physical and Biogeochemical Regionalization of the Southern Ocean and the CCAMLR Zone 48.1 - Testa, Giovanni; Piñones, Andrea; Castro, Leonardo R. (Frontiers in Marine Science, 2021)
The Southern Ocean plays a major role in the Earth’s climate, provides fisheries products and help the maintenance of biodiversity. The degree of correspondence between physical and biogeochemical spatial variability and regionalization were investigated by calculating the main physical factors that statistically explained the biogeochemical variability within the Southern Ocean and the 48.1 zone of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). The mean value of physical and biogeochemical variables was estimated during austral summer within a grid of 1° × 1° south of 50°S. The regionalization was developed using both non-hierarchical and hierarchical clustering method, whereas BIO-ENV package and distance-based redundancy analysis (db-RDA) were applied in order to calculate which physical factors primarily explained the biogeochemical spatial variability. A total of 12 physical and 18 biogeochemical significant clusters were identified for the Southern Ocean (alpha: 0.05). The combination of bathymetry and sea ice coverage majorly explained biogeochemical variability (Spearman rank correlation coefficient: 0.68) and db-RDA indicated that physical variables expressed the 60.1% of biogeochemical variance. On the other hand, 14 physical and 16 biogeochemical significant clusters were identified for 48.1 CCAMLR zone. Bathymetry was the main factor explaining biogeochemical variability (Spearman coefficient: 0.81) and db-RDA analysis resulted in 77.1% of biogeochemical variance. The correspondence between physical and biogeochemical regions was higher for CCAMLR 48.1 zone with respect to the whole Southern Ocean. Our results provide useful information for both Southern Ocean and CCAMLR 48.1 zone ecosystem management and modeling parametrization.